ANALISIS PEMBANGKIT TENAGA LISTRIK MENGGUNAKAN BIOGAS DI PT. KENCANA TIARA GEMILANG - Abi Fitrabiandi; Unggul Wibawa; Tri Nurwati (Jurnal Mahasiswa TEUB, 2023)
Renewable energy is one of the energy sources that can meet energy needs. One of the renewable energy sources is biogas. Biogas is the fermentation process of organuk materialto produce methane gas. Biogas can be converted into other energy,one of which is electrical energy. In this research will be conducted an analysis of the potential of biogas in PT. KTG. The biogaswill be converted into electrical energy. The material of making biogas this time is garden waste that will be put in the digester.The waste will decay and produce methane gas in the digester. The gas will be put into the generator as fuel to be converted intoelectricity. In the results of the experiment, the potential of biogas in PT. KTG is enough to run one division. Of the 1m3 biogasproduced can produce electricity of 3.42 kWh. Because the type of garden waste is varied, so the electricity generated has apercentage of 56% match with the literature. The costs incurred during the trial period when using electricity from PLN amountedto Rp. 25,523.03, - and when using electricity converted from biogas was Rp. 8,600.-. Keywords: biogas, electric power, generator